The effects of social density, spatial density, noise, and office views on perceived personal space in the virtual workplace - Jicol, Crescent; Taulo, Gerald; Goldie, Cora; Lloyd-Esenkaya, Tayfun; Hynes, Ruth; Paradise, Caroline; Proulx, Michael J.; de Sousa, Alexandra A. (Frontiers in Computer Science, 2023)
Here we sought to understand how perceived personal space is influenced by a number of variables that could influence Indoor Environmental Quality (IEQ); specifically, we tested how different levels of social density, spatial density, noise presence, and type of view impact the appreciation of personal space in a shared office environment. We employed virtual reality (VR) to simulate shared and single occupancy offices and devised a novel measure of personal space estimation. We also used a traditional personal space satisfaction score. Participants experienced greater perceived personal space when 1) in a sparsely populated rather than a dense office, 2) in a private office rather than an open plan office, and 3) having any view outside of the office. We did not find an effect of the presence of noise or increased social density (with spatial density held constant) on the perception of personal space.